Analysing preservice teachers' enactment of the UDL framework to support diverse students in a remote teaching context. (June 2023) - Barahona, Malba; David, Viviana; Gallegos, Francisca; Reyes, José; Ibaceta-Quijanes, Ximena; Darwin, Stephen
Abstract: Internationally, the investigation of inclusive education in foreign language teaching and foreign language teacher education is a relatively new phenomenon. Part of this imperative has been the pressing need to research how teachers perceive inclusion and learn to support a diverse range of students. Responding to this challenge, this paper reports on the results of a case study that investigated the perceptions and attitudes toward inclusion of a group of Chilean preservice teachers of English (n = 6) enacting the Universal Design for Learning (UDL) in ELT. The study drew on qualitative data generate through interviews, focus group discussion and an artefact analysis, and was conducted within a remote teaching context due to COVID pandemic during 2020 and 2021. The outcomes suggested that preservice teachers conceptualised inclusion as 'not-segregation', expressing positive attitudes toward diversity and a commitment to principles of inclusion in their teaching. The enactment of UDL allowed participants to diversify the representation of contents and making language more comprehensible. However, participants also experienced frustration and anxiety as they felt their practices were sometimes ineffective. The findings also made visible the complex challenges and struggles preservice teachers confront as they attempt to teach inclusively, particularly in remote learning environments.